Identifikasi Ras Fisiologis Fusarium oxysporum f.sp. cubense Berdasarkan Sifat Kompatibel Secara Vegetatif dan Pembentukan Bahan Volatil - Arif Wibowo; Suryanti Suryanti; Christanti Sumardiyono (Universitas Gadjah Mada, 2002)
Race characterization of F. oxysporum Schlecht. f.sp. cubense (E.F. Smith) Snyd. & Hans. by determining disease reaction is difficult because the result may be biased due to the variability of growing condition. This study is aimed to identify physiological races of F. oxysporum f.sp. cubense in banana plantation in the province of Daerah Istimewa Yogyakarta by examining the relation of the fungal pathogen isolates. The identification of physiological races of F. oxysporum f.sp. cubense was based on vegetative compatibility groups (VCGs). The research was conducted in The Laboratory of Mycology Faculty of Agriculture GMU on March to November 2000. Observation of heterokarion formed by the mutant of F. oxysporum f.sp. cubense on selective medium was carried out in order to identify the compatibility of two different fungal isolates. Nitrate non utilizing (nit) mutants obtained without mutagen were used as the label. Nit mutant obtained from the same wild type isolates could form heterokarion on minimal agar medium containing NaNO3 as nitrogen source. Eleven isolates of F. oxysporum f.sp. cubense have been isolated from several cultivars of banana. Vegetative compatibility tests showed that of 11 eleven isolates, there were six different group VCGs where four of them formed volatile compound in rice medium whereas two of them did not.